Application of Zeolite, Pumice, and Activated Carbon for Lowering Water Hardness and Total Dissolved Solids (TDS) - Wulandari, Retno; Damayanti, Ken Ima; Annur, Shohifah; Irawati, Lusi; Irmawan, Ari; Syah, Fikri Firman (International Journal of Advanced Multidisciplinary, 2025)
Water is one of the most essential natural resources for living organisms. Tonjong Village is a residential, agricultural, and fish farming area. According to the test results from the Environmental Laboratory Unit of the Environmental Agency, the groundwater quality in Tonjong Village shows the following physical and chemical parameters: TDS 3352 mg/L, TSS 11 mg/L, pH 6.85, Hardness (CaCO?) 1100 mg/L, COD 9.34 mg/L, and BOD 2.40 mg/L. This study aims to reduce TDS and water hardness using a multi-stage treatment method. The research consists of three stages: the preliminary stage, the equipment fabrication stage, and the testing stage. The results indicate a decrease in TDS from 3352 mg/L to 1380 mg/L and a reduction in hardness using material variation 2 from 1100 mg/L to 752.5 mg/L.